2022
DOI: 10.1007/s11356-022-20141-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between renewable energy consumption, carbon emissions, output, and export in industrial and agricultural sectors: evidence from China

Abstract: This paper examines the long-term and short-term relationships between renewable energy consumption, output and export, and CO 2 emissions in China over the period 1990–2020 from the perspective of industry and agriculture using econometric methods. The results of the study found that there is a long-run relationship and there is a causality between these variables, indicating that renewable energy consumption, output, and export are related to CO 2 emissions. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…As the world's energy demand continues to grow, human overexploitation of fossil fuels has led to increasingly severe ecological and environmental pollution. 1,2 It has become a broad consensus in the international community to work together to address the global problems brought by the "high carbon economy". 3 Developing bio-refining and partially replacing petroleum and fossil energy is an essential technical path to achieving carbon neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…As the world's energy demand continues to grow, human overexploitation of fossil fuels has led to increasingly severe ecological and environmental pollution. 1,2 It has become a broad consensus in the international community to work together to address the global problems brought by the "high carbon economy". 3 Developing bio-refining and partially replacing petroleum and fossil energy is an essential technical path to achieving carbon neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…Single-country datasets have been analyzed by numerous studies. Hao [ 64 ] looks at the industrial and agricultural perspectives on the long- and short-term links between the use of RE, output, export, and CDE in the case of China. The study confirmed that, while the use of RE has a positive impact on the environment, output and exports have negative effects, and that there is a two-way causal relationship over the long run between the use of RE, output, exports, and CDE.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…These insights emphasize the role of green technology investment and renewable technology adoption in reducing carbon emissions and enhancing sustainability in the manufacturing industry (Rusmayadi et al, 2023). Hao (2022) examines the relationship between renewable energy consumption, carbon emissions, output, and export in China's industrial and agricultural sectors. The econometric analysis reveals a long-term causal relationship between these variables, indicating that renewable energy consumption has a favorable impact on the environment.…”
Section: Economic and Policy Considerations Cost-benefit Analysis Of ...mentioning
confidence: 99%
“…The study suggests that economic growth and energy consumption (renewable and non-renewable) in related industries significantly influence CO2 emissions. This analysis provides a basis for the development of renewable energy and the implementation of emission control policies, highlighting the necessity of considering the impact of economic activities on carbon emissions (Hao, 2022). The integration of renewable energy into the manufacturing industry presents a viable solution for reducing carbon emissions and advancing towards carbon neutrality.…”
Section: Economic and Policy Considerations Cost-benefit Analysis Of ...mentioning
confidence: 99%